Strategy for Implementing the Disaster-Safe Education Unit Program After the M5.0 Earthquake on September 18, 2024 in Bandung - Lasmana, Ujang Dede (International Journal of Integrative Sciences, 2024)
This study discusses the implementation strategy of the Disaster-Safe Education Unit Program (Satuan Pendidikan Aman Bencana/SPAB) in the Bandung area after the M5.0 earthquake that occurred on September 18, 2024. This earthquake caused damage to various educational units in Bandung Regency, Garut Regency, and West Bandung Regency, and highlighted the importance of disaster preparedness in the school environment. This study aims to understand how SPAB is implemented and formulate appropriate strategies to improve the preparedness of educational units in disaster-prone areas. Qualitative analytical methods were used with data collection techniques in the form of observation, interviews, and literature studies. The results of the study indicate that SPAB requires a strategy that includes increasing school capacity, providing earthquake-resistant infrastructure, collaborating with related institutions, and regular disaster socialization and simulations. Risk analysis using the PESTLE tool and Hazards & Vulnerability Assessment (HVA) was also identified as an important method in risk scanning in educational units. Policy recommendations include increasing the mitigation budget, formulating SPAB standards, and developing inter-sectoral collaboration. This study emphasizes the importance of sustainable SPAB implementation to ensure the safety and sustainability of education in earthquake-prone areas